Narrativas sobre estrategias de afrontamiento y apoyo del círculo social en un grupo de adolescentes de padres separados (2022)
In order to know the aspects associated or derived from the process of marital separation and its influence in the period of adolescence, the present investigation was developed in order to describe and analyze the narratives on coping strategies and support of the social circle in a group of adolescents with separated parents. Therefore, the study was carried out with the participation of 4 adolescents, 2 female and 2 male, children of separated parents, between the ages of 18 and 20, who reside in the city of Bogotá.